Personal Predictors of Future Medical Workers Adaptation to the Conditions of Professional Activity - Halian , Andrii (Insight: the psychological dimensions of society, 2024)
The purpose is to study the predictors that forecast the structure of the adaptation process of future medical workers to the conditions of professional activity. It is assumed that adaptation to the conditions of professional activity of future medical workers among others is provided by latent factors that are the result of the interaction of personality traits and qualities. Methods: testing by “Social-Psychological Adjustment Questionnaire” (Rogers & Dymond, 1954). Subjective resources for overcoming difficulties in various areas of mental activity were studied using “Ways of Coping Questionnaire” (Folkman, Lazarus, 1980). Internal psychological regulatory resources involved in the adaptation process were assessed using the Action Control Scale (Kuhl, 2001). The versions of the questionnaires validated on the Ukrainian sample were used. The total research sample was 84 future medical workers (college students) of the specializations “General Medicine”, “Nursing”. The sample is homogeneous, formed randomly. Results. Latent factors (predictors) that ensure the adaptation process of future medical workers were identified: “Support seeking” (F1), “Friendliness” (F2), “Conformity” (F3), “Anti-stress” (F4), “Rationalism” (F5), “Self-analysis of situations” (F6). The share of predictors involved in the formation of adaptation processes of future medical workers was determined. Four of the six factors were included in the multiple analysis regression model. Two predictors (“rationalism” t = 1.299; p = .201 and “self-analysis of the situation” t = .356; p = .356) were not included in the regression models due to the lack of statistical significance of their t-test. Discussion and conclusions. Future medical workers have been diagnosed with a medium level of adaptive capacity, which helps them adapt to the conditions of professional activity at the stage of primary professionalization. The factors that form the structure of the adaptive capacity of future medical workers were identified. Using the method of linear multiple regression, the share of each factor in ensuring the effectiveness of the adaptation process was determined. The share of “friendliness” (32.00%) in the explanation of “adaptation” is the highest. The share of “conformity” is slightly lower (20.00%). “Support seeking” accounts for only 11.56% of the variance explained. The smallest share in the regression model belongs to the predictor “antistress” – 3.72% of the explained variance. The prospect of further research on the problem highlighted in the article is the validation of the factor model, which requires a confirmatory analysis.
Keywords: adaptation, multiple equations, personal resources, self-regulation, coping strategies, predictors, personality traits.